Biographie et histoire dans la jeune République. - Naomi Wulf (Transatlantica)
This paper aims at assessing the relatively recent rediscovery of biography as a historical genre and its place in the historiography of the Early Republic. Beyond biography as a traditional genre, many historians have reinvented a biographical approach to history in which they do not merely tell a life‑story, but study individuals as they reveal and reflect the period in which they live. This renewed approach is particularly telling of the early years of the American Republic when a sense of individualism emerged within mass democratic culture.